The role of the Rho GTPases in neuronal development. - Govek, E; Newey, S; Van Aelst, L (2005)
Our brain serves as a center for cognitive function and neurons within the brain relay and store information about our surroundings and experiences. Modulation of this complex neuronal circuitry allows us to process that information and respond appropriately. Proper development of neurons is therefore vital to the mental health of an individual, and perturbations in their signaling or morphology are likely to result in cognitive impairment. The development of a neuron requires a series of steps that begins with migration from its birth place and initiation of process outgrowth, and ultimately leads to differentiation and the formation of connections that allow it to communicate with appropriate targets. Over the past several years, it has become clear that the Rho family of GTPases and related molecules play an important role in various aspects of neuronal development, including neurite outgrowth and differentiation, axon pathfinding, and dendritic spine formation and maintenance. Given the importance of these molecules in these processes, it is therefore not surprising that mutations in genes encoding a number of regulators and effectors of the Rho GTPases have been associated with human neurological diseases. This review will focus on the role of the Rho GTPases and their associated signaling molecules throughout neuronal development and discuss how perturbations in Rho GTPase signaling may lead to cognitive disorders.